Penerapan Model Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS) untuk Meningkatkan Motivasi Belajar Tema Hidup Rukun pada Siswa Kelas II - Suti, Ni Ketut (Universitas Pendidikan Ganesha, 2018)
This study aimed at improving the students’ motivation to learn by implementing Think-Pair-Share (TPS) type of cooperative learning model.. The subjects were 24 second grade students of SD N 1 Darmasaba in the first semester of the academic year 2016/2017. The type of this research was classroom action research (CAR). The data collected by observation method. The data obtained were analyzed using descriptive statistical analysis. Based on the results of data analysis, it can be concluded that the application of Think-Pair-Share (TPS) type of cooperative learning model can improve the learning motivation of second grade students of SD N 1 Darmasaba. It can be seen from the improvement of the average of students’ learning motivation from cycle I which was 18 to 23 in cycle II. The classical completeness of students also increased from 75% in the first cycle to 92% in the second cycle.